2017
DOI: 10.1097/md.0000000000007353
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cataract surgery in patients with uveitis

Abstract: To evaluate the visual outcomes of cataract surgery in patients with uveitis, and to determine risk factors for the recurrence of uveitis and postoperative complications.Eighty patients with uveitis who underwent phacoemulsification with intraocular lens (IOL) implantation were included in this retrospective study. We analyzed the following data: patient characteristics, medications used, visual acuity, and complications of cataract surgery.The mean ± standard deviation time from cataract surgery to the last v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
0
16
1
1
Order By: Relevance
“…Zhang Y et al have found that uveitis recurred in 14 eyes (18.9%) within 3 months and in ammation recurred in 34 eyes (45.9%) in the whole follow-up period [29]. Balta O et al have determined that the incidence of postoperative recurrence of uveitis was 52.7% in 48 patients underwent cataract surgery during 4 years of follow-up [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang Y et al have found that uveitis recurred in 14 eyes (18.9%) within 3 months and in ammation recurred in 34 eyes (45.9%) in the whole follow-up period [29]. Balta O et al have determined that the incidence of postoperative recurrence of uveitis was 52.7% in 48 patients underwent cataract surgery during 4 years of follow-up [1].…”
Section: Discussionmentioning
confidence: 99%
“…Balta O et al have found that the BCVA of 20/40 or better was achieved in 81.8% eyes (n = 18) in idiopathic anterior uveitis, 80.0% eyes (n = 8) in herpes simplex virusassociated anterior uveitis, 90.0% eyes (n = 9) in Fuchs' heterochromic iridocyclitis, and 100% (n = 13) in anterior uveitis associated with collagen vascular diseases over the 4 years of follow-up [1]. However, it is worth noting that uveitis is usually not quiescent after cataract surgery, and the recurrence of uveitis can be observed at an uncertain time [1,29].…”
Section: Introductionmentioning
confidence: 99%
“…Cystoid macular edema occurs after surgery in the patients who suffered posterior capsule rupture (accidentally or by Nd-YAG laser capsulotomy); some authors state that perioperative systemic therapy is protective against those complications [ 6 , 7 ]. Prolonged eye inflammation after surgery is relatively rare, especially if heparin-surface-modified intraocular lenses are implanted [ 8 ]. Postoperative rising of intraocular pressure can occur frequently in these patients [ 2 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…It had been proved by experiments those materials with high hydrophilicity cause less postoperative inflammatory reactions due to reduced adhesion of surface cells and proteins ( Roesel et al, 2008 ). Therefore, HSM was thought to improve the uveal biocompatibility of the material, which had also been demonstrated in many clinical trials, especially for patients with preoperative uveitis ( Krall et al, 2014 ; Zhang et al, 2017 ). Unfortunately, HSM has not shown a special effect on the prevention of PCO ( Ronbeck and Kugelberg, 2014 ) through long-term observation.…”
Section: Intraocular Lens Surface Modification Materialsmentioning
confidence: 99%